Dynamics of Femoral Bone Remodelling in Well Fixed Total Hip Arthroplasty. a 20-Year Follow-Up of 20 Hips. Issue 2 (March 2014) - Stucinskas, Justinas; Clauss, Martin; Tarasevicius, Sarunas; Wingstrand, Hans; Ilchmann, Thomas
The aim of our study was to investigate the dynamics of cortical thinning around well fixed cemented Muller straight stems without osteolysis at different time periods during long term follow-up. We investigated patients operated on for osteoarthritis with a cemented Muller straight stem, all with more than 15 years follow-up and no radiological signs of osteolysis. Cortical thinning in 20 THA hips (19 patients) followed for a mean of 20 (16 to 22) years was measured medially and laterally at six levels from the first postoperative, five, 10 years and the last follow-up x-rays. Sixty percent of observed cortical thinning occurred during the first five postoperative years, which was more evident proximally. We conclude that significantly greater cortical bone loss occurs around cemented Muller straight stems during the first five years, than is seen subsequently. We feel that this is a non-pathological process mainly related to the Muller straight stem.